Bilateral agreement for the period 2012/2014 Socrates Programme: higher education Erasmus between Universidade Lusíada de Lisboa and Universitat Politècnica de Catalunya - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme. - Erasmus subject area: Architecture.